OPTIMASI PENGGUNAAN ASAM AMINO IKAN LEMURU DAN PGPR AKAR EDAMAME TERHADAP KUALITAS HASIL PADA TANAMAN EDAMAME - Wardah, Nabila Ika; Wardana, Rudi; Mukhlisin, Ilham; Jumiatun, Jumiatun (Institute of Computer Science (IOCS), 2026)
Edamame is an agricultural commodity with high economic value and potential for development. The pod filling stage plays an important role in determining the success of pod production with premium quality standards. This study was conducted from April to August 2024 on the grounds of the Jember State Polytechnic. The objective of this study was to examine the effect of amino acid application and Plant Growth Promoting Rhizobacteria (PGPR) on edamame production and quality. This study used a Factorial Randomised Block Design (RAKF) with two treatment factors. The first factor was the concentration of amino acids derived from lemuru fish, consisting of five levels: 0 ml/L (control), 5 ml/L, 10 ml/L, 15 ml/L, and 20 ml/L. The second factor was the concentration of PGPR, consisting of two levels: 0 ml/L (as a control) and 150 ml/L. The results of the study data showed that the amino acid treatment produced significantly different results in terms of total pods, pods with two seeds, and the percentage of pods with seeds. Meanwhile, the PGPR treatment had a significantly different effect on the observed variables of total pods and filled pods. The amino acid treatment at a concentration of 15 ml/L was able to increase the number of filled pods and the percentage of filled pods. Meanwhile, the PGPR treatment at a concentration of 150 ml/L was able to increase the percentage of filled pods.